Many rotors of combined material airframe - GE JIARONG; HU JIGEN; ZHANG HUIZI (2017)
The utility model relates to a many rotors of combined material airframe is by equipment compartment, cantilever, undercarriage, rotor, anticollision circle with hang and constitute. The equipment compartment is located, and the anticollision circle is located the outside, and the equipment compartment is connected by the cantilever with the anticollision circle, and is provided with the motor mounting platform on the cantilever for lay motor and rotor. Undercarriage and equipment compartment sub -unit connection to hang structural having arranged of intermediate truss, can be used to lay the airborne equipment or be used for the medical treatment rescue. Compare with the metal organism, simple structure is satisfying under service conditions's the condition, and the combined material organism has the obvious heavy advantage that subtracts, but because weight loss reduce energy consumption. 本实用新型涉及种复合材料多旋翼飞行器机体，由设备舱、悬臂、起落架、旋翼、防撞圈和吊挂构成。设备舱位于内，防撞圈位于外侧，设备舱和防撞圈由悬臂连接，且悬臂上设置有电机安装平台，用于安放电机和旋翼。起落架与设备舱下部连接，并在中间桁架结构上布置